Nordic Model of Subregional Co-operation - Grzela, Joanna (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
Nordic co-operation is renowned throughout the world and perceived as the collaboration of a group of countries which are similar in their views and activities. The main pillars of the Nordic model of co-operation are the tradition of constitutional principles, activity of public movements and organisations, freedom of speech, equality, solidarity, and respect for the natural environment. In connection with labour and entrepreneurship, these elements are the features of a society which favours efficiency, a sense of security and balance between an individual and a group. Currently, the collaboration is a complex process, including many national, governmental and institutional connections which form the “Nordic family”.